2010
DOI: 10.1103/physrevlett.104.203001
|View full text |Cite
|
Sign up to set email alerts
|

Structure Effects in Angle-Resolved High-Order Above-Threshold Ionization of Molecules

Abstract: We present energy-resolved angular distributions of photoelectrons generated in above-threshold ionization (ATI) of nonaligned diatomic molecules N2 and O2 in high-intensity short laser pulses, with emphasis on the most energetic part of the spectra. The angular distribution for photoelectrons with energy of 10U(p) (U(p): ponderomotive energy), i.e., the plateau cutoff in ATI spectra, is found to be broader in O2 than in N2. Resorting to the analyses from both an S-matrix theory and an intuitive semiclassical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
30
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 27 publications
2
30
0
Order By: Relevance
“…[10][11][12][13]. It has also been shown that structural information of the target can be retrieved using short light pulses [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13]. It has also been shown that structural information of the target can be retrieved using short light pulses [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…For example, HHG can be used to obtain ultrashort attosecond pulses [4,5] and to image atomic or molecular structures [6][7][8][9][10], HATI can be used to investigate molecular structures [11][12][13][14][15] and dynamics [16], and NSDI shows that the multielectron ionization in an intense laser field is not always sequentially one by one [17][18][19][20][21][22]. It is often the case that these three phenomena, i.e., HHG, HATI, and NSDI, may occur during a single recollision process, implying that we may treat them under a unified theoretical frame.…”
Section: Introductionmentioning
confidence: 99%
“…From an experimental point of view, ZWRs have already been exploited for the interpretation of spectral data concerning the predissociation of IBr [27]. To the best of our knowledge, although EPs have not yet been used in experimental works involving molecular systems, they have recently been directly observed in an open quantum composite of a single atom and a high-Q cavity mode [28].…”
Section: Introductionmentioning
confidence: 99%